Strategi Komunikasi Pemasaran Dalam Meningkatkan Penjualan Pada Omah Kopi Mandiri Tulungangung Melalui Media Sosial Instagram - Nur Dina (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Marketing strategy is very important so that the communication delivered runs effectively and builds public awareness according to the goals that are achieved. Having an increase in sales is much desired by all businesses in running their companies and also accompanied by following technological developments today. Many businesses have followed technological developments by using Instagram social media in running their business by promoting products through Instagram. Omah Kopi Mandiri Tulungagung is one of the businesses that has used Instagram social media in carrying out marketing strategies to increase sales with Instagram. The results of this research at Omah Kopi Mandiri can be concluded that Omah Kopi Mandiri Tulungagung has used features on Instagram but not all features are used so that the marketing strategy of using Instagram to increase sales is only able to increase sales slightly. There are several obstacles faced, the main one is not having experts and creators in managing Instagram owned by Omah Kopi Mandiri Tulungagung. Keywords: Marketing Strategy, Sales, Instagram